Analysis of Public Perception of Prucinta Products at PT Prudential Asuransi Binjai Branch - Sindi Sindi; Tri Inda Fadhila Rahma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The public's view of the company is an important part to pay attention to. Because the public's view of the company will affect the product offerings offered to the public. The good image of the company will affect consumer behavior. Because, perception becomes a measure of consumer behavior. Sharia insurance is an effort to protect and help each other among a number of people through investment in the form of assets through tabarru' funds which provide a pattern of taking to face certain risks or dangers through contracts that are in accordance with sharia. The success of Islamic insurance companies cannot be separated from the role of the community regarding the importance of insurance. The issue that will be reviewed in this journal is the public's understanding and opinion of sharia insurance. This study aims to find out how the public's opinion on the existence of sharia insurance in Binjai. The method used in this study is a qualitative method with data collection techniques with literature studies and interviews from the Binjai community.